Against the dark - Seagal, Steve; Goldfine, Philip B.; Klickstein, Mathew; Crudo, Richard; Steamroller Productions presents (Los Angeles, CA : Steamroller Productions, 2009)
Infected vampires suck the world dry of blood. A few of the last survivors are trapped in a hospital full of flesh feeders. Their only hope is Tao, a Katana master who, along with his squad of ex-military vigilantes, will now have to kill the vampires or be converted in a battle that will be the last stand to save humanity
Title from title screen
Special features: Fighting the shadows: behind the scenes of Against the dark
Director of photography, William Trautvetter ; edited by, Tim Silano ; music by, Philip White
Cast: Steven Seagal, Tanoai Reed, Linden Ashby, Jenna Harrison, Danny Midwinter, Keith David
DVD format
Dolby digital
Keywords: Vigilantes -- Drama; Vigilantes -- Drama; Veterans -- Drama; Survivalism -- Drama